A novel proxy-oriented public auditing scheme for cloud-based medical cyber physical systems. (April 2020) - Xu, Zhiyan; He, Debiao; Wang, Huaqun; Vijayakumar, Pandi; Raymond Choo, Kim-Kwang
Abstract: Cloud-based medical cyber-physical system (MCPS) is attracting more and more attention, since it can break through the limitations of time, space and object, and allow doctors to make accurate telemedicine diagnosis for patients. However, since medical information is directly related to the safety of patients' lives and property, it has become an urgent problem to ensure the integrity and availability of medical data. To solve the above problems, many integrity auditing schemes have been proposed in recent years. Unfortunately, most existing schemes have security flaws or poor performance. Very recently, Zhang et al. proposed an identity-based proxy-oriented auditing scheme for checking the integrity of medical data, and claimed that their scheme was secure. However, we find that their scheme fails to achieve its purpose since it is vulnerable to the user impersonation attack and misusing delegation attack. we propose a new proxy-oriented public auditing scheme to fix the security vulnerabilities. Security analysis and performance evaluation demonstrate that our proposed scheme greatly reduces the communication and computation costs while ensuring a novel security level. Compared with Zhang et al.'s scheme, our scheme is more suitable for applications in cloud-based MCPS.